2021
DOI: 10.1371/journal.pone.0261761
|View full text |Cite
|
Sign up to set email alerts
|

Working from home and productivity under the COVID-19 pandemic: Using survey data of four manufacturing firms

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has impacted the world economy in various ways. In particular, the drastic shift to telework has dramatically changed how people work. Whether the new style of working from home (WFH) will remain in our society highly depends on its effects on workers’ productivity. However, to the best of our knowledge, the effects of WFH on productivity are still unclear. By leveraging unique surveys conducted at four manufacturing firms in Japan, we assess within-company prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…In onsite environments, there are consistent relationship development opportunities (e.g., adjacent offices, shared lunch areas), whereas telework environments require planning to establish contact. And quality communication opportunities were important [17][18]. Song and Gao [39] Heiden et al [40] Vander Elst et al [28] Wohrmann and Ebner [30] Wohrmann and Ebner [30] Erro-Garces et al [ In drawing on the proactive work design model, work design conditions were the most studied component regarding telework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In onsite environments, there are consistent relationship development opportunities (e.g., adjacent offices, shared lunch areas), whereas telework environments require planning to establish contact. And quality communication opportunities were important [17][18]. Song and Gao [39] Heiden et al [40] Vander Elst et al [28] Wohrmann and Ebner [30] Wohrmann and Ebner [30] Erro-Garces et al [ In drawing on the proactive work design model, work design conditions were the most studied component regarding telework.…”
Section: Resultsmentioning
confidence: 99%
“…Song and Gao [39] Heiden et al [40] Vander Elst et al [28] Wohrmann and Ebner [30] Wohrmann and Ebner [30] Erro-Garces et al [ In drawing on the proactive work design model, work design conditions were the most studied component regarding telework. For example, working conditions [17], dedicated home office spaces [18,31], flexibility [31][32], and organizational support [17,34] were seen as important contributors to decent work for employees engaging in telework practices. This makes contextual sense given that many studies focused on understanding what drivers effected wellbeing in workplaces where telework was merely a reflection of the same work and work practices occurring offsite.…”
Section: Resultsmentioning
confidence: 99%
“…When the organization’s performance and productivity are under discussion in the WFH system, opinions are often contradictory. A study on WFH during the COVID-19 pandemic showed that WFH is associated with low employee productivity, and most workers experienced declines in productivity, probably due to their inadequate preparation for WFH under the sudden shock of the pandemic [ 9 ] (p. 21). Poor communication and lack of a well-developed setup for WFH were also mentioned among the factors that negatively influence employee productivity.…”
Section: Literature Review Ad Research Questionsmentioning
confidence: 99%
“…This study brings contributions in the field of remote working, a research field that receive a huge attention after the COVID-19 pandemic [ 8 , 9 , 21 , 24 ]. Our findings are bringing significant insights into the factors that influence the technical and social self-assessed performance of the employees working in remote systems.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…In view of these broad repercussions, it is desirable that the mathematical and computational studies of the Covid-19 pandemic go beyond the transmission of the physical infection and consider its more nuanced effects in the distinct age and socioeconomic segments of the population, which requires a multiscale and multifaceted approach. [1,2] In addition, they should consider also the effects of the measures to curb the spread of coronavirus, such as social distancing and lockdowns, on the mental health of the population, [3][4][5] and on work productivity, [6][7][8] which can be thought of as a second-order effect of the virus infection. Interestingly, the surge of loneliness associated to those prevention measures may be related to the widespread rising of authoritarianism seen today since, as pointed out long ago by Hannah Arendt, "the chief characteristic of the mass man is not brutality and backwardness, but his isolation and lack of normal social relationships".…”
Section: Introductionmentioning
confidence: 99%